Comparison of Standard and Tubeless Percutaneous Nephrolithotomy in a Tertiary Care Hospital in Eastern Nepal - Thakur, Deepak Kumar (Birat Journal of Health Sciences, 2018)
Introduction PCNL is a minimally invasive technique for treatment of renal and upper ureteral stones and has gone modiﬁcations like tubeless, total tubeless, mini and ultra mini PCNL. Objective To compare eﬃcacy, safety and outcome of tubeless PCNL with standard PCNL. Methodology The study was conducted from January 2017 to December 2017 involving 50 patients undergoing PCNL randomized into standard PCNL group (S group) and tubeless PCNL group (T group) each arm containing 25 patients. Patients with congenital renal anomalies, solitary functioning kidney, previous renal surgery, clinically signiﬁcant residual stones/fragments, perforation of pelvi-calyceal system and requiring conversion were excluded. Data analyzed using SPSS 20, chi-square test and Student's t test was used where appropriate. A p-value of <0.05 was considered signiﬁcant. Results Mean age, mean stone size, preoperative hemoglobin level and creatinine level in group S and T were comparable. Similarly postoperative hemoglobin level and creatinine level in groups S and T were comparable. The mean operating time in group S was 99.38± 16.24min and 89.38 ± 12.27min in group T ( p=0.02). Postoperatively, VAS in group S was 5.25± 0.94 and 2.88± 1.68 in group T ( p<0.001). Complication occurred in 9 patients in S group as postoperative anemia (hemoglobin <10gram/dl)-3 cases, superﬁcial surgical site infecon-4 and urine leak-2 while it was seen in 3 patients in T group as stoma site hematoma-2 and anemia-1 (p= 0.04). Three patients in group S and 1 patient in group T respectively required transfusion (p= 0.82). Postoperative analgesic requirement in S and T groups were 13.08± 2.39 and 9.03± 2.44 grams of paracetamol respectively ( p<0.001). The hospital stay was 3.79± 0.58 days in S group and 2.54 ± 0.50 days in T group (p<0.001). Conclusion Tubeless PCNL is a safe option in selected cases. It is associated with signiﬁcantly less postoperative pain, analgesic requirement, postoperative complication and shorter duration of hospital stay minimizing treatment cost. BJHS 2018;3(1)5 : 366 - 369